2018
DOI: 10.1016/s1473-3099(18)30073-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic sequencing for surveillance of drug resistance in tuberculosis in highly endemic countries: a multi-country population-based surveillance study

Abstract: SummaryBackgroundIn many countries, regular monitoring of the emergence of resistance to anti-tuberculosis drugs is hampered by the limitations of phenotypic testing for drug susceptibility. We therefore evaluated the use of genetic sequencing for surveillance of drug resistance in tuberculosis.MethodsPopulation-level surveys were done in hospitals and clinics in seven countries (Azerbaijan, Bangladesh, Belarus, Pakistan, Philippines, South Africa, and Ukraine) to evaluate the use of genetic sequencing to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 24 publications
2
124
0
2
Order By: Relevance
“…Although the basis of this diversity is unclear, it is hypothesized that either the gene is situated in a hot spot region, or that it is a consequence of the lack of DNA mismatch repair mechanisms in MTB [32]. For the mutations in pncA, 40/61 point mutations conferring pyrazinamide resistance that we found have been reported previously [33][34][35], and to our knowledge, 21 novel mutations and all 11 frameshift changes (insertions or deletions) were first found in this study. There are also other unknown resistance mechanisms responsible for the resistance phenotype, such as mutations in rpsA gene, however, low frequency of rpsA gene mutations showed that rpsA gene mutation was not the main mechanism of pyrazinamide resistance [36,37].…”
Section: Discussionsupporting
confidence: 51%
“…Although the basis of this diversity is unclear, it is hypothesized that either the gene is situated in a hot spot region, or that it is a consequence of the lack of DNA mismatch repair mechanisms in MTB [32]. For the mutations in pncA, 40/61 point mutations conferring pyrazinamide resistance that we found have been reported previously [33][34][35], and to our knowledge, 21 novel mutations and all 11 frameshift changes (insertions or deletions) were first found in this study. There are also other unknown resistance mechanisms responsible for the resistance phenotype, such as mutations in rpsA gene, however, low frequency of rpsA gene mutations showed that rpsA gene mutation was not the main mechanism of pyrazinamide resistance [36,37].…”
Section: Discussionsupporting
confidence: 51%
“…The introduction of WGS in routine diagnostics was found accurate (species identification accuracy: 99%; drug susceptibility accuracy: 96% for eight drugs) and rapid (72 h for WGS vs 28 days for DST only), allowing to replace seven different molecular assays and accelerating reporting time . WGS was also successfully used for drug resistance surveillance purposes …”
Section: Molecular Dstmentioning
confidence: 99%
“…161,162 WGS was also successfully used for drug resistance surveillance purposes. 163,164 The advances in performances of NGS workflow (from DNA extraction to data analysis) allowed to improve WGS for 'real-time' routine diagnosis in direct clinical samples, with MTB complex detection accuracy of >97%. Prediction of DST was obtained from 62% of cases, with complete concordance with phenotypic drug susceptibility reference testing.…”
Section: Sequencingmentioning
confidence: 99%
“…Since its discovery by Robert Koch in 1832, Mycobacterium tuberculosis (MTB) remains a great health threat to the global population, particularly in Southeast Asian and some African countries [63]. Nearly ten million new MTB infections have been recognized annually during the past 5 years according to a WHO TB report.…”
Section: Organoid Modeling Of Pulmonary Tuberculosismentioning
confidence: 99%